Reaktorji za biološka zdravila - Škof, Nina (Matrika, 2017)
The development of bioreactors is one of the major challenges in raising biological samples, cells and more generally in biotechnology today. In the article, three main types of biological reactors used in the production of biopharmaceuticals are presented. These are stirred tank, bubble column and airlift reactors. Firstly, the production of biological medicinal products is briefly described, followed by the description of each of the bioreactor types. Further on, the role of hydrodynamics in biological processes that take place inside the reactor is discussed.
Keywords: biološka zdravila; biopharmaceuticals; bioreactors; bioreaktorji